National Geographic readers. In the ocean - Szymanski, Jennifer (Washington, DC : National Geographic Kids, 2018)
Describes the plants and animals that live in the world's oceans.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Ocean -- Juvenile literature; Marine animals; Marine plants; Ocean; Electronic books- OSLIS; Picture books; Electronic books